Bentuk, Makna Dan Fungsi Giling Pinang, Rukun Tarahan Pada Sangku Tambak Raja Di Masyarakat Hindu Kaharingan - Sulandra Sulandra (Jurnal Penelitian Agama Hindu, 2026)
This study examines the significance of ritual symbolism in the religious practices of the Hindu Kaharingan community, focusing on the roles of Giling Pinang and Rukun Tarahan within the Sangku Tambak Raja. These ritual elements function not merely as offerings but also embody symbolic, theological, and social meanings that mediate the relationship between humans, Ranying Hatalla Langit, and ancestral spirits, while reinforcing the community’s collective identity. The study aims to analyze the forms, meanings, and functions of Giling Pinang and Rukun Tarahan within the ritual structure of Sangku Tambak Raja. This research employs a qualitative approach with cultural and sociological perspectives. Data were collected through participant observation, in-depth interviews with basir, pisor, customary leaders, offering makers, and ritual practitioners, as well as documentation. Informants were selected purposively based on their roles and knowledge of the ritual. Data were analyzed using an interpretative qualitative framework involving data reduction, data display, and conclusion drawing. The findings reveal that Giling Pinang is constructed in a-shaped form using betel leaves, lime, areca nut, and tobacco, arranged according to standardized ritual procedures, while Rukun Tarahan consists of traditional hand-rolled cigarettes prepared in odd numbers and symbolically positioned within the ritual setting. Both elements carry symbolic–theological meanings rooted in Panaturan mythology and Kaharingan cosmology and are interpreted by the community as media of spiritual communication linking humans, ancestors, and divine entities. Furthermore, these ritual symbols function as mechanisms for transmitting religious values, strengthening cultural identity, and fostering social cohesion through collective participation in the Basarah ritual. This study contributes to the broader discourse on Hindu ritual studies in the Indonesian context by demonstrating that Giling Pinang and Rukun Tarahan operate as integrated symbolic structures that sustain cosmological beliefs, local theological frameworks, and the socio-cultural continuity of the Hindu Kaharingan community.